SEKOLAH DASAR ALAM DI PONTIANAK - Pirmansyah, Pirmansyah; Kalsum, Emilya; Caesariadi, Tri Wibowo (JMARS: Jurnal Mosaik Arsitektur, 2026)
Indonesia ranked 68th in the 2022 PISA assessment, with scores of 379 in mathematics, 398 in science, and 371 in reading. These results reflect several challenges in the education system, such as limited teacher competence, inadequate learning facilities, and a misalignment between curriculum and student needs. Unengaging teaching methods also contribute to low student motivation. Additionally, in the 2022 Environmental Performance Index (EPI), Indonesia ranked 164th out of 180 countries, indicating serious issues related to ecosystems, environmental health, and climate policy. In Pontianak, similar educational and environmental challenges persist, despite ongoing efforts such as improving educational infrastructure and increasing community involvement in environmental issues. As an alternative approach, the Nature School concept is proposed to integrate education with environmental awareness. This approach emphasizes character building, environmental understanding, and experiential learning through nature-based activities. North Pontianak, with its abundant natural resources, is considered suitable for implementing this concept. The Nature-Based Elementary School is designed with an integrated-with-nature concept to support early sustainable education. Facilities such as gardens and educational cultivation areas encourage student interaction with the environment. The design incorporates sustainable materials, a clear layout, interactive circulation, and optimizes natural lighting and ventilation suited to Pontianak"™s tropical climate, aiming to create healthy and eco-friendly learning spaces.